PENGEMBANGAN BUCERGAM (BUKU CERITA BERGAMBAR) UNTUK MENINGKATKAN KARAKTER GOTONG ROYONG SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS I SEKOLAH DASAR - Salwah Rini Apriyani; Bramianto Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to produce picture story book products to improve the character of mutual cooperation of grade 1 elementary school students. The subjects of this study were grade 1 students of SDIT El Wafa. The type of research used in this study is research and development with the ADDIE model which consists of the stages of analysis, design, development, implementation and evaluation. The subjects of this study were grade 1 students of SDIT EL Wafa. The results of this research on developing picture story books are: (1) picture story media as a learning tool for Pancasila education, especially in the subject of mutual cooperation at school; (2) the media developed is in the form of a book with interesting illustrations in accordance with the development of grade 1 elementary school students; From the results of the feasibility test conducted by three validators, namely media experts, language experts, and bucergam material experts, an average percentage of 94.19% was obtained, with a very feasible category. The results of the teacher's response obtained an average percentage of 90.6%, while the results of the trial through the student response questionnaire for the small group test obtained a percentage of 84%, and the large group test obtained a percentage of 85%. The results before and after the treatment increased by 1,019 with a practical category.